(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article analyzes and engages with the performance Fálica by Brazilian visual artist and playwright Ana Luisa Santos, which proposes a countersexual and counter-hegemonic perspective, criticizing the cis-heteropatriarchy as the dominant regime of power. Simultaneously, it connects with the artist’s proposition where bankruptcy, downfall, and inversion emerge as essential attributes to be contemplated. This connects with the current movement of toppling, removing, resignifying, intervening, replacing, and toppling colonial/racist/patriarchal monuments, hegemonic statues that represent past horrors but whose presence in public spaces updates them.